Menelisik Status Sosial Ekonomi Calon Walikota dan Wakil Walikota Dalam Membangun Ekspektasi Ekonomi dan Preferensi Politik Masyarakat di Kota Mataram - Haeril Amri; Himawan Sutanto; Subhan Purwadinata (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to understand the socio-economic status of the mayoral and vice mayoral candidates to strengthen the economic aspirations and political preferences of the people of Mataram City. This study employs a qualitative approach to collect data through in-depth interviews with local residents and an analysis of local socio-economic dynamics. The research findings indicate that the socio-economic status of the candidates has a significant impact on public expectations regarding economic policies and political preferences. The community tends to choose candidates with a strong economic background, as they are perceived to have better prospects for economic growth.